2020
DOI: 10.1111/jce.14351
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of ventricular arrhythmia guided by a high‐density grid catheter

Abstract: Introduction: Minimal data exist on the Advisor HD Grid (HDG) catheter and the Precision electroanatomic mapping (EAM) system for ventricular arrhythmia (VA) procedures. Using the HDG catheter, the EAM uses the high-density (HD) wave mapping and best duplicate software to compare the maximum peak-to-peak bipolar voltages within a small zone independent of wavefront direction and catheter orientation. This study aimed to summarize the procedural experience for VAs using the HDG catheter.Methods: Clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Clinical studies have demonstrated the usefulness of the HDG catheter in patients undergoing CA for atrial fibrillation and ventricular arrhythmias in structural heart disease 4–6,8,24 . A novel feature of the HDG catheter is an ability to create bipolar EGMs at orthogonal directions to account for the direction of wavefront propagation 4 . Previous studies have shown that the electrode orientation in relation to wavefront activation is in part responsible for the bipolar EGM 21,26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies have demonstrated the usefulness of the HDG catheter in patients undergoing CA for atrial fibrillation and ventricular arrhythmias in structural heart disease 4–6,8,24 . A novel feature of the HDG catheter is an ability to create bipolar EGMs at orthogonal directions to account for the direction of wavefront propagation 4 . Previous studies have shown that the electrode orientation in relation to wavefront activation is in part responsible for the bipolar EGM 21,26 .…”
Section: Discussionmentioning
confidence: 99%
“…3D mapping was performed using the Ensite™ Precision/Velocity™ electroanatomic mapping (EAM) system (Abbott Medical), with interior projection setting set at 7 mm and bipolar signal filtering at 30–500 Hz. The Ensite EAM incorporates the HD Wave solution and best duplicate algorithm to select the EGM with the largest amplitude at orthogonal bipoles 4,8 within a 1‐mm zone. All ablations in the HDG cohort were performed using the irrigated, contact force sensing TactiCath™ SE catheter, with a contact force between 10 and 25 g. Power settings utilized were as per operator discretion, typically 25–40 W for atrial ablation and 30–40 W for ventricular ablation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach to mapping and ablation of scar-related ventricular tachycardia (VT) has been described previously. 9) 10) Procedures were performed under either conscious sedation or general anaesthesia. An SL3 sheath (Abbott Medical, Abbott Park, IL, USA) was used to perform coronary sinus venography and a decapolar catheter inserted into the coronary sinus.…”
Section: Methodsmentioning
confidence: 99%
“…Our approach to mapping and ablation of scar‐related VT has been described previously 16,20 . Procedures were performed under either conscious sedation or general anesthesia 3,12,17 .…”
Section: Methodsmentioning
confidence: 99%